Mitochondrial DNA variants in a cohort from Argentina with suspected Leber’s hereditary optic neuropathy (LHON) - Buonfiglio, Paula Inés (2023)
The present study investigates the spectrum and analysis of mitochondrial DNA (mtDNA) variants associated with Leber hereditary optic neuropathy (LHON) in an Argentinean cohort, analyzing 3 LHON-associated mitochondrial genes. In 32% of the cases, molecular confirmation of the diagnosis could be established, due to the identification of disease-causing variants. A total of 54 variants were observed in a cohort of 100 patients tested with direct sequencing analysis. The frequent causative mutations m.11778G>A in MT-ND4, m.3460G>A in MT-ND1, and m.14484T>C in MT-ND6 were identified in 28% of the cases of our cohort. Secondary mutations in this Argentinean LHON cohort were m.11253T>C p.Ile165Thr in MT-ND4, identified in three patients (3/100, 3%) and m.3395A>G p.Tyr30Cys in MT-ND1, in one of the patients studied (1%). This study shows, for the first time, the analysis of mtDNA variants in patients with a probable diagnosis of LHON in Argentina. Standard molecular methods are an effective first approach in order to achieve genetic diagnosis of the disease, leaving NGS tests for those patients with negative results.